Transmission Electron Microscopy (TEM) Study of the Oocyst of Eimeria tenella - Devi, Irungbam Karuna; Devi, Y. Geeta; Chanu, Kh. Victoria; Ali, M. Ayub; Tewari, Jully Gogoi; Prava, M.; Malsawmkima, David; Patra , Gautam (International Journal of Poultry Science, 2010)
The present work describes isolation, cell wall preparation, morphological as well as molecular detection of oocyst of Eimeria tenella. Based on transmission electron microscopy, the oocyst of this species showed the outer and inner wall without veil forming bodies; cross section of sporozoites with different organelles and macrogamete structure at ultrastructural level. Polymerase Chain Reaction (PCR) based on Internal Transcribed Spacer 1 (ITSI) regions of ribosomal DNA (rDNA) demonstrated 270 bp specific for E. tenella. Results of this study provide the basis for further ultrastructural studies of the organism. The present study also suggested that morphological characteristics along with molecular identification are prerequisite for validation and identification of Eimeria species.